Data interpretation made easy : for medical students and junior doctors - Sharma, Neel (Radcliffe Publishing, 2013)
The ability to interpret and synthesise medical data is essential for doctors, yet it is a skill which can be difficult to master. This book focuses on developing this skill by presenting an array of case-based themes considering interpretation of blood results, X-rays, ECGs and CT images in medicine with discussion of evidence-based practice. The concise, list-based text aids easy comprehension and images provide the much needed link from raw data to evidence-based care and management.